Eksistensi Hukum Tanah Lingko Mbehal di Wilayah Administrasi Kecamatan Boleng Kabupaten Manggarai Barat - Matilde Ayu Jehuru; Sukardan Aloysius; Petornius Damat (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The purpose of this research is to analyze the legal existence of Lingko Mbehal land in the administrative area of Boleng District, West Manggarai Regency. The type of research used by the author is empirical normative legal research. The sources of legal materials used in this research are primary and secondary legal materials. The method of processing legal materials through 3 (three) stages, namely editing, coding and systematization of data which is then analyzed descriptively qualitatively. Based on the results of the research, the structure of the mbehal customary functionaries now consists of: tua golo, tua gendang and tua batu The loss of tua pasa and penggawa is due to the fact that the lingko or customary land in mbehal has become private land or property rights. Due to the belief of the mbehal indigenous people, the existence of the lingko means that the tua pasa and penggawa also exist, because the duties of the two customary functionaries are closely related to land. the current implementation of the functions of the mbehal customary functionaries are: First, Tua Gendang functions as the head of the traditional house. Secondly, Tua Golo usually leads nempung or joint deliberations. Thirdly, Tua Pasa only functions when clearing land. Fourth, the penggawa is responsible for distributing the lingko to the community because Tua Pasa is only responsible for clearing the land. Finally, Tua Batu functions as the head of the family at the branch family level. The legal position of lingko mbehal land is: Firstly, the opening of lingko mbehal has several stages, namely nempung (deliberation), preparation for the division of the lingko (haju pasa and tuak bongko), implementation of the lingko lodok (teing hang/torok manuk, weri haju pasa and division of the lingko. Secondly, when planting, materials such as manuk sepang, manuk bakok and manuk welu are prepared. During the harvest season, the mbehal community calls it "uma randang dara wini latung". Thirdly, the Mbehal Lingko consists of two types of Lingko, namely religious Lingko and randang Lingko.